FREQUENCY, ASSOCIATED RISK FACTORS AND ANGIOGRAPHICAL CLASSIFICATION OF CORONARY ARTERY ECTASIA (CAE) AND CORONARY ARTERY ANEURYSM (CAA) IN ST ELEVATION MYOCARDIAL INFARCTION(STEMI) PATIENTS UNDERGOING PRIMARY PERCUTANEOUS CORONARY INTERVENTION (PPCI)) - Raja, Waseem; Samore, Naseer Ahmed; Kamran, Javeria; Saif, Mohsin; Jaffri, Syed Khawar Abbas; Bhatti, Qamar Zaman; Rauf, Amer (Pakistan Armed Forces Medical Journal, 2019)
Objective: To study the frequency, associated risk factors and morphological distribution of Coronary Artery Ectasia (CAE) and Coronary Artery Aneurysm (CAA). Study Design: Descriptive cross sectional study. Place and Duration of Study: Department of Cardiology, Armed Forces Institute of Cardiology & National Institute of Heart disease (AFIC/NIHD) Rawalpindi from Jul 2018 to Jul 2019. Methodology: All patients who underwent Primary Percutaneous Coronary Intervention (PCI) for ST elevation Myocardial Infarction (STEMI) at our institute were considered for this descriptive cross sectional study. A consecutive sampling method was used and inclusion/exclusion criteria was applied. Number of patients having ectatic coronary arteries, ectasia distribution and morphological classification was done by trainee researcher after studying the coronary angiograms. Demographic information, symptoms and risk factors were also documented. Data recording, storage, assessment and analysis was done by using SPSS software version 21. Results: A total 1354 patients diagnosed with STEMI underwent PPCI during the study period and Coronary Artery Ectasia (CAE) was diagnosed in 31 patients (2.2%), out of that 5 (16.13%) patients had Coronary Artery Aneurysm (CAA). Mean age of patients was 58.32 (± 11.22). Hypertension was the commonest preexisting risk factor 9 (29%) followed by Diabetes Mellitus (DM) 4 (12.9%). Left Anterior Descending (LAD) artery was ectatic vessel in majority of our study group. Ectatic coronaries were classified as fusiform 20 (64.52%) and saccular 11 (35.48%) on the basis of shape and in type 1-4 (type 1=16.13%, type 2=35.48%, type 3=32.26%, type 4=16.13%). Statistically significant association (p-value=0.003) was found between infarct related artery....